Ir‐Based Alloy Nanoflowers with Optimized Hydrogen Binding Energy as Bifunctional Electrocatalysts for Overall Water Splitting. Issue 6 (24th April 2019) - Lv, Fan; Zhang, Weiyu; Yang, Wenxiu; Feng, Jianrui; Wang, Kai; Zhou, Jinhui; Zhou, Peng; Guo, Shaojun
Abstract: Hydrogen production through proton exchange membrane water electrolyzers (PEMWE) requires more active and stable electrocatalysts in acidic media. Herein, a class of Ir‐based alloys is reported with flower‐like structure as excellent electrocatalysts both for hydrogen and oxygen generation in acid. Specially, the IrNi alloy nanoflowers (IrNi NFs) present the best hydrogen evolution reaction (HER) performance, revealed by a low Tafel slope and overpotential at current density of 10 mA cm −2, exceeding the commercial Pt/C. It is discovered that alloying Ir with Ni can decrease the hydrogen binding energy (HBE) of Ir metal, resulting in almost 2.5 times increase in the HER intrinsic activity of IrNi NFs than Ir NFs. The IrNi NFs catalyst is also highly efficient in oxygen evolution reaction with mass activity of 379 A g −1 Ir at 1.51 V versus reversible hydrogen electrode. Furthermore, the overall water‐splitting devices using the IrNi NFs as catalysts for both cathode and anode show a low cell voltage of 1.60 V at 10 mA cm −2 and long‐term stability within 1000 cycles. This work uncovers that HBE optimization is the key of enhancing HER activity on Ir‐based alloys and these Ir‐based NFs hold great promise in future application in the PEMWE. Abstract : A group of Ir‐based alloys with flower‐like structure are made as excellent electrocatalysts both for hydrogen and oxygen generation in acidic media, and it is discovered that alloying Ir with Ni or Co can bring down the hydrogen binding energy of Ir metal, resulting in the enhanced hydrogen evolution reaction intrinsic activity of Ir metal.